Well-defined core-shell nanostructural block copolymer supported recyclable Bronsted acidic ionic liquid catalyst for the synthesis of biodiesel. (5th November 2020) - Jiang, Jian; Wang, Songmeng; Kong, Yuanfang; Yan, Wei; Chen, Hao; Liu, Lingyan; Chang, Weixing; Li, Jing
Graphical abstract: A well-defined block copolymer supported Bronsted acidic ionic liquid catalyst was developed and displayed excellent catalytic activity (biodiesel yield > 99%) and good recyclability (6 cycles) in the esterification or transesterification of palmitic acid and methanol or ethanol, thus highly efficiently synthesizing the biodiesel. Highlights: The hydrophobic PS corona can restrict water entering into core-catalytic active center. The P4VP core anchored onto acidic ionic liquid constructs a nano-reactor. The PS- b -P4VP nanoreactor can efficiently catalyze the esterification reaction. The catalysts 3-6 can be well recycled by simple centrifugation separation. The core cross-linked micelles are relatively stable with less catalyst leaching. The catalyst recycled for 6 times can be easily regenerated and reused. Abstract: A series of Bronsted acidic ionic liquid catalysts was synthesized by anchoring 1-(3-sulfopropyl)pyridinium trifluoromethanesulfonate onto the stable core-shell micelles, which were formed by cross-linking various chain length ratios PS- b -P4VP in toluene with 1, 4-dibromobutane. These catalysts display excellent catalytic activity in the esterification or transesterification of palmitic acid or glycerol tripalmitate with methanol or ethanol to synthesize the biodiesel (yield > 99%) in the presence of 4 mol% catalyst loading. Furthermore, the biodiesel yield was maintained about 90% even with a water content of 10 wt% corresponding to the total weight of reaction system. More importantly, these supported catalysts with core-shell structure could be recycled for 5–6 times (5 cycles: yield 89.3%, 6 cycles: yield 84%) only by simple centrifugation without appreciating activity decrease.